Mother's Strategy on Child Mentoring in Using the Internet - Dyva Claretta; Yuli Candrasari; Irwan Dwi Arianto (Nusantara Science and Technology Proceedings)
The rapid growth of internet resulted in increasing internet users in Indonesia. Today the internet is easily found in Indonesian family homes. Therefore, many early age children who already know the internet. Even the children are deliberately facilitated by their parents to be able to easily access the internet. The condition is of course very worrying because of the impact of the internet is also great for the development of children. Some studies also illustrate that the internet disrupts relationships within the family. This study examines how Mother's role in protecting her children against the invasion of the internet. This study uses a Computer-Mediated-Communication (CMC) perspective which states that computers have changed the shape of human social relationships. This brings with it social and cultural consequences in human life. This research was conducted by using the qualitative method with maternal and child analysis unit as a research subject. The technique of data retrieval is done by using in-depth interview and observation participant whereas technique analyzes data use descriptive analysis. The results of this study indicate that Mother still assesses the existence of the internet in the house needed to support the activities of his children, including in helping complete school tasks. Therefore, parents easily provide support facilities so that their children can easily access the internet. Furthermore, this research also shows that in performing assistance there are three categories that apply the rules in using the internet, doing active mediation, and activity online together.